Marketing and the customer value chain : integrating marketing and supply chain management /: integrating marketing and supply chain management. (2022) - Fotiadis, Thomas; Folinas, Dimitris, 1970-; (Author of Marketing and the customer value chain), Vasileiou, Konstantinos; Konstantoglou, Aggeliki
No abstract available